Risk factors for first-time acute myocardial infarction patients in Trinidad - M. Bahall; T. Seemungal; G. Legall (BMC, 2018)
Abstract Background The relative importance of coronary artery disease (CAD) risk varies globally. The aim of this study was to determine CAD risk factors for acute myocardial infarction (AMI) among patients in public health care institutions in Trinidad using a case-control type study design. Methods The sample comprised 251 AMI patients hospitalized between March 1, 2011 and April 30, 2012 and 464 age- and sex-matched non-AMI patients with no terminal or life-threatening illness and who did not undergo treatment for CAD. SPSS version 19 was used for data analysis that included chi-square tests, unadjusted and adjusted odds ratios (OR) and conditional multiple binary logistic regression. Results There was no difference in age between AMI and non-AMI patients (p = 0.551). Chi-square test revealed that clinical and lifestyle variables including stressful life, diabetes, hypertension, hypercholesterolaemia, ischaemic heart disease (IHD), a family history of IHD (p ≤ 0.001), smoking (p = 0.007) and alcohol consumption (p = 0.013) were associated with AMI; sex (p = 0.441), ethnicity (p = 0.366), age group (p = 0.826) and renal failure (p = 0.487) were not. Both unadjusted and adjusted (for age) ORs showed that the odds of hypertension, IHD and alcohol consumption were greater among AMI patients than among non-AMI patients for males; diabetes and IHD for females; and that the odds of a stressful life was greater among non-AMI patients and were the same for both groups with respect to sex, age > 45 years, hypercholesterolemia, renal insufficiency, and family history of IHD. Conditional multiple logistic regression showed that smoking [OR: 0.274, p ≤ 0.001, 95% CI for OR (0.140, 0.537)], a stressful life [OR: 2.697, p ≤ 0.001, 95% CI for OR (1.585, 4.587)], diabetes [OR: 0.530, p = 0.020, 95% CI for OR (0.310, 0.905)], hypertension [OR: 0.48, p = 0.10. 95% CI for OR (0.275, 0.837)] and IHD [OR: 0.111, p ≤ 0.001, 95% CI for OR (0.057, 0.218)] were the only useful AMI predictors. Conclusions Smoking, diabetes, hypertension, IHD and decrease stress are useful AMI predictors.